The Effect of a Student Aid Reform on Graduation: A Duration Analysis - Iida Häkkinen; Roope Uusitalo (Uppsala University, Department of Economics, 2003)
In this paper we evaluate the changes in the times-to-degree at the Finnish universities in the 1990s. In particular, we evaluate the effect of the 1992 student aid reform that was intended to shorten the duration of university studies. We find that the student aid reform had only a modest effect, and that this effect was limited to the fields with long median durations. Most of the decline in the observed times-to-degree can be explained by an increase in the unemployment rate that reduced student employment opportunities.
urn:nbn:se:uu:diva-4462
Keywords: I22; 330; Times-to-degree; university education; student aid; duration analysis; Studium; Studienfinanzierung; Dauer; Finnland